A interferência do uso de amplificador de voz na dose vocal de professoras com disfonia - Joana Perpétuo Assad (2017)
Objectives: To perform an integrative literature review about the vocal doses and the behavior of these measurements in different communicative situations and to test the interference of the use of voice amplification in the parameters of the vocal dose of teachers with dysphonia in the professional environment. Method:The integrative review was guided by the following question: "What are the types of vocal doses and what is the behavior of these measurements in different communicative situations?". For selection of the articles, the national and international literature, published in all languages, was searched, using MEDLINE, LILACS, IBECS and ISI (Web of Science) databases. Articles published over the last twenty one years (1995 to 2016) and available in full were included. To evaluate the interference of vocal amplifier use in the vocal dose of female teachers with dysphonia, 15 female and elementary school teachers from Belo Horizonte Public School, with a mean age of 38.6 years, were evaluated. Teachers used the voice dosimeter during lecture activity, in two different moments, one without and one with the use of the voice amplifier, with the same students and in the same classroom. The average recording time was 96 minutes. The phonatory data were stored in the portable unit of the voice dosimeter and analyzed through the equipment software (VoxLog). The intensity (dBSPL), the fundamental frequency (FO), the percentage of vocal fold vibration on the recording time (%), the phonation time (in seconds) and the vocal doses (cycle and distance doses) were analyzed. Results:On the integrative review, fifteenstudies met the established criteria. The majority of the articles studied teachers, once they belong a vulnerable group for dysphonia. The doses found were phonation percent, time dose, cycle dose, distance dose, energy dissipation dose and radiated energy dose. Comparing the vocal dose of dysphonic teachers with and without microphone, a statistically significant difference in intensity, fundamental frequency, cyclic dose and distance parameters were found. Conclusion:The vocal dose increase is associated to an excessive and prolonged voice use in teaching activity, to the environmental noise, the large prosodic variation in speech and the self-perception of vocal fatigue. Factors such as voice rest and use of voice amplifier indicate a decrease of vocal dose. The vocal amplification, however, does not change the amount of phonation used by teachers in teaching activity.